Marketing Strategy of the Zakat and Waqf Management Study Program - Ely Masykuroh; Anton Sudrajat (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2025)
The phenomenon of competition and the emergence of many campuses with various study programs and the lack of enthusiasts for zakat and waqf management study programs is a necessity for study programs to carry out marketing activities by formulating appropriate strategies. This research method is qualitative with data analysis techniques through data reduction, data presentation, and conclusion drawing. The results of this study offer alternative marketing strategies for zakat and waqf management study programs, namely cost advantage, differentiation, and focus.